2016
DOI: 10.1097/hjh.0000000000000798
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying elevated SBP differ with adiposity in young adults

Abstract: Objectives:The positive association between adiposity and hypertension is well recognized. However, not all overweight individuals have elevated blood pressure (BP). Moreover, different factors may be associated with high BP in normal-weight versus overweight individuals. The aim of the current study was to examine the influence of adiposity on the relationship between SBP and underlying haemodynamic mechanisms in young adults.Method:Data from 2502 patients were available from the Enigma study. Detailed demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…49 Cardiac output is also elevated in overweight or obese subjects, and weight gain in childhood is associated with both an increase in stroke volume and sBp. 50 However, more recently, we have shown that in overweight individuals, cardiac output is elevated irrespective of the level of Bp, and it is actually the level of peripheral vascular resistance that distinguishes between individuals with elevated versus normal brachial sBp 51 ( Figure 2). these data suggest that the mechanisms underlying elevated sBp in young adults depend on body size, which may hold important, additional implications for treating isH in young people.…”
Section: Mechanisms Of Ish In Young Peoplementioning
confidence: 96%
See 1 more Smart Citation
“…49 Cardiac output is also elevated in overweight or obese subjects, and weight gain in childhood is associated with both an increase in stroke volume and sBp. 50 However, more recently, we have shown that in overweight individuals, cardiac output is elevated irrespective of the level of Bp, and it is actually the level of peripheral vascular resistance that distinguishes between individuals with elevated versus normal brachial sBp 51 ( Figure 2). these data suggest that the mechanisms underlying elevated sBp in young adults depend on body size, which may hold important, additional implications for treating isH in young people.…”
Section: Mechanisms Of Ish In Young Peoplementioning
confidence: 96%
“…Algunas personas obesas mantienen la PAS baja a través de una resistencia vascular periférica notablemente menor. Datos provenientes de Middlemiss et al 51 Figura 3. Esquema descriptivo de la serie de adaptaciones hemodinámicas propuesta mediante la cual el gasto cardíaco elevado deriva en hipertensión sostenida.…”
Section: Mecanismos De La Hsa En Personas Jóvenesunclassified
“…13 In the same group of patients, the influence of cardiac output on SBP was more important in normal-weight adults, as compared with overweight patients, where peripheral resistance was more important. 14 In the elderly ARIC population reported by Tanaka and colleagues, 4 the increase in ET contributed most to the model predicting PP, outnumbering aortic stiffness and wave reflections. This effect is most pronounced in the oldest age group (≥80 years) and is somewhat surprising, challenging the traditional view that the increase of PP with aging is mostly related to a combined effect of unfavorable alterations of the arterial system.…”
mentioning
confidence: 90%
“…In young relatively healthy untreated individuals, sex, stroke volume, wave reflections (AIx), and aortic stiffness (cfPWV) explained 37%, 6%, 2%, and 2% of the variability of brachial PP, respectively . In the same group of patients, the influence of cardiac output on SBP was more important in normal‐weight adults, as compared with overweight patients, where peripheral resistance was more important . In the elderly ARIC population reported by Tanaka and colleagues, the increase in ET contributed most to the model predicting PP, outnumbering aortic stiffness and wave reflections.…”
mentioning
confidence: 91%
“…Prev i ous studies have extensively investigated the predictive value of different adiposity measures for blood pressure (BP), hypertension, and other cardiovascular diseases [10][11][12][13][14][15]. BMI is widely used to estimate the prevalence of obesity within a population.…”
Section: Introductionmentioning
confidence: 99%